Порівняльні характеристики стандартів мобільного зв’язку - Бондарчук, Є. В. (ХНУРЕ, 2023)
This article provides an overview of the evolution of mobile communication standards from GSM to 5G, highlighting their unique features and capabilities. It discusses the advantages and disadvantages of each standard, as well as the limitations they present. The main topics covered in the article include GSM (2G), 3G, 4G and 5G